Menjelajahi estetika dan fungsi: Tinjauan mendalam tentang dunia arsitektur - Sulistyana, Anisya Noor (Maliki Interdisciplinary Journal, 2024)
This article aims to provide an in-depth look at important aspects of the world of architecture, in particular focusing on the complex relationship between aesthetics and function in the context of spatial design. More than just creating physical structures, architecture has a profound role to play in shaping the physical environment in which humans interact. One of the main elements in this process is aesthetics, the visual layering of elements and art in architectural design. The right aesthetics can evoke emotions, create a unique atmosphere, and provide an immersive experience for space occupants. However, aesthetics is not the only relevant consideration in successful architecture. Functions also play a very important role. A building that is beautiful but does not meet its functional requirements will only be less effective. Therefore, this article will also explore how harmony between aesthetics and function is very important in the architectural design process. In this article, we will investigate how architects combine aesthetic elements with appropriate function, as well as how innovative developments in conceptual thinking continue to shape the field of architecture. We will discuss concrete examples of how aesthetic and functional aspects have been integrated in leading architectural projects. By looking at the latest trends and contemporary approaches in the industry, this article will explain how important it is to understand and apply these principles holistically in order to create spaces that are not only visually stunning, but also capable of fulfilling their functional purpose well, creating a harmonious balance between aesthetics and function.